Aortopulmonary Window With Pulmonary Atresia and Interrupted Aortic Arch: A Very Rare Triad. Issue 6 (November 2019) - Shahbah, Doaa A.; Herrick, Nicole L.; El-Said, Howaida; Lamberti, John; Murthy, Raghav
Aortopulmonary window (APW) is a rare lesion, accounting for 0.2% to 0.6% of all congenital heart diseases. We report a rare case of an infant with APW, interrupted aortic arch, and pulmonary atresia with intact interventricular septum and right ventricle–dependent coronary circulation. This report describes the anatomy of this lesion set, the complex surgical palliation that was required, and the management of postoperative complications.